1999
DOI: 10.1096/fasebj.13.10.1207
|View full text |Cite
|
Sign up to set email alerts
|

Differential T cell response in central and peripheral nerve injury: connection with immune privilege

Abstract: The central nervous system (CNS), unlike the peripheral nervous system (PNS), is an immune-privileged site in which local immune responses are restricted. Whereas immune privilege in the intact CNS has been studied intensively, little is known about its effects after trauma. In this study, we examined the influence of CNS immune privilege on T cell response to central nerve injury. Immunocytochemistry revealed a significantly greater accumulation of endogenous T cells in the injured rat sciatic nerve than in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
82
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(88 citation statements)
references
References 57 publications
5
82
0
1
Order By: Relevance
“…Another common characteristic of injured CNS is the increased presence of infiltrating immune cells that have been suggested to contribute to the pathology and the spread of damage (2). However, some studies have shown that in the event of an acute injury or chronic neurodegenerative conditions, T cells are recruited by and accumulate in the CNS (41,42), where they rescue neurons from degeneration. Moreover, a well-controlled boost of autoimmune activity following injury increases the number of surviving neurons (43).…”
Section: Discussionmentioning
confidence: 99%
“…Another common characteristic of injured CNS is the increased presence of infiltrating immune cells that have been suggested to contribute to the pathology and the spread of damage (2). However, some studies have shown that in the event of an acute injury or chronic neurodegenerative conditions, T cells are recruited by and accumulate in the CNS (41,42), where they rescue neurons from degeneration. Moreover, a well-controlled boost of autoimmune activity following injury increases the number of surviving neurons (43).…”
Section: Discussionmentioning
confidence: 99%
“…The number of Cop-1-reactive T cells that home to the CNS is increased after CNS injury (55). It therefore seems likely that Cop-1-reactive T cells recognize self-antigens presented at the site of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Cop-1, acting as an immunogen, may serve both purposes-neuroprotection from neuronal insult and therapy for autoimmune diseases. Presumably it achieves this dual purpose by evoking a ''safe'' T cell response, which provides, on the one hand, the beneficial autoimmune T cell response needed for neuroprotection (1,2,7,23,24) and, on the other hand, the immune modulation required for avoidance of autoimmune disease (25).…”
Section: Discussionmentioning
confidence: 99%
“…R ecent studies in our laboratory demonstrated that the death of neurons after traumatic injury to the central nervous system (CNS) can be delayed and reduced by reinforcing a T cell immune response directed against myelin-associated self-antigens (1)(2)(3). With the use of optic nerve injury of adult rats as a model, we found that, irrespective of their antigen specificity, T cells accumulate at the lesion site after injury, and their numbers increase after their passive transfer (1,2,4).…”
mentioning
confidence: 88%
See 1 more Smart Citation